Body composition and fitness in elite Spanish children tennis player - Berdejo-del-Fresno, D.; Rodriguez, G. V.; Rave, J. M. G.; Moreno, L. A.; Rey-Lopez, J. P. (Journal of Human Sport & Exercise, 2010)
The aims of this study were to describe body composition and physical fitness changes during a whole-season in elite children tennis players. A total of 7 elite children tennis players participated in the study. Whole body composition by dual energy X-ray absorptiometry (DXA) and physical fitness were assessed during a season. Subjects increased lean and bone percentage, and decreased abdominal fat and total body fat percentage